Loss of CAPS2/Cadps2 leads to exocrine pancreatic cell injury and intracellular accumulation of secretory granules in mice - Sato, Yotaroh; Tsuyusaki, Miho; Takahashi-Iwanaga, Hiromi; Fujisawa, Rena; Masamune, Atsushi; Hamada, Shin; Matsumoto, Ryotaro; Tanaka, Yu; Kakuta, Yoichi; Yamaguchi-Kabata, Yumi; Furuse, Tamio; Wakana, Shigeharu; et al. (Frontiers in Molecular Biosciences, 2022)
The type 2 Ca2+-dependent activator protein for secretion (CAPS2/CADPS2) regulates dense-core vesicle trafficking and exocytosis and is involved in the regulated release of catecholamines, peptidergic hormones, and neuromodulators. CAPS2 is expressed in the pancreatic exocrine acinar cells that produce and secrete digestive enzymes. However, the functional role of CAPS2 in vesicular trafficking and/or exocytosis of non-regulatory proteins in the exocrine pancreas remains to be determined. Here, we analyzed the morpho-pathological indicators of the pancreatic exocrine pathway in Cadps2-deficient mouse models using histochemistry, biochemistry, and electron microscopy. We used whole exosome sequencing to identify CADPS2 variants in patients with chronic pancreatitis (CP). Caps2/Cadps2-knockout (KO) mice exhibited morphophysiological abnormalities in the exocrine pancreas, including excessive accumulation of secretory granules (zymogen granules) and their amylase content in the cytoplasm, deterioration of the fine intracellular membrane structures (disorganized rough endoplasmic reticulum, dilated Golgi cisternae, and the appearance of empty vesicles and autophagic-like vacuoles), as well as exocrine pancreatic cell injury, including acinar cell atrophy, increased fibrosis, and inflammatory cell infiltration. Pancreas-specific Cadps2 conditional KO mice exhibited pathological abnormalities in the exocrine pancreas similar to the global Cadps2 KO mice, indicating that these phenotypes were caused either directly or indirectly by CAPS2 deficiency in the pancreas. Furthermore, we identified a rare variant in the exon3 coding region of CADPS2 in a non-alcoholic patient with CP and showed that Cadps2-dex3 mice lacking CAPS2 exon3 exhibited symptoms similar to those exhibited by the Cadps2 KO and cKO mice. These results suggest that CAPS2 is critical for the proper functioning of the pancreatic exocrine pathway, and its deficiency is associated with a risk of pancreatic acinar cell pathology.